Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

For any positive integer $n$, consider $$\int_{0}^\infty\frac{(r^2-1)r^{n+1}}{(r^2+1)^{n+3}}dr.$$ I would like to show that it is positive. I try to write it as $$\int_{0}^\infty\frac{(r^2-1)r^{n+1}}{(r^2+1)^{n+3}}dr=\int_{0}^\infty\frac{r^{n+1}}{(r^2+1)^{n+2}}dr-2\int_{0}^\infty\frac{r^{n+1}}{(r^2+1)^{n+3}}dr,$$ but I am not sure that it helps.

EDIT: According to sjasonw, the integral may not be positive as I think. I would be happy to see a proof showing that it's not positive.

share|improve this question
2  
Let $u = r^2 + 1$, so that $r^2 = u - 1$ and $dr = 2rdu$. Suppose $n$ is even. Then the integral is $$ \frac{1}{2} \int_1^\infty \frac{(u-2)(u-1)^{n/2}}{u^{n+3}}du. $$ Let's say $n = 2$. We get $$ \frac{1}{2} \int_1^\infty \frac{u^2 - 3u + 2}{u^{5}}du = \frac{1}{2}\left(\frac{1}{2} - 3\cdot\frac{1}{3} + 2\cdot\frac{1}{4} \right) = 0. $$ –  user29743 Dec 22 '12 at 4:15

3 Answers 3

up vote 3 down vote accepted

Let $I$ denote the integral, then we have that $$I = \int_{0}^\infty\frac{(r^2-1)r^{n+1}}{(r^2+1)^{n+3}}dr = \underbrace{\int_{0}^\infty\frac{r^{n+3}}{(r^2+1)^{n+3}}dr}_J - \underbrace{\int_{0}^\infty\frac{r^{n+1}}{(r^2+1)^{n+3}}dr}_K$$ Consider $J$. Let $r=1/t$, we then get that $$J = \int_{\infty}^0 \dfrac{1/t^{n+3}}{(1/t^2+1)^{n+3}} \left(- \dfrac{dt}{t^2} \right) = \int_{0}^\infty\frac{t^{n+1}}{(t^2+1)^{n+3}}dt = K$$ Hence, $$I=0$$

share|improve this answer
    
That's exactly what I need. Thanks a lot! –  Paul Dec 22 '12 at 4:20

Mathematica gives

$$\int\frac{\left(r^2-1\right)r^{n+1}}{\left(r^2+1\right)^{n+3}}dr=-\frac{r^{2+n} \left(1+r^2\right)^{-2-n}}{2+n}$$

share|improve this answer

If $$\int \frac{(r^2-1)r^{n+1}}{(r^2+1)^{n+3}}dr=I$$

$$\int \frac{(r^2-1)r^{n+1}}{(r^2+1)^{n+3}}dr=\int \frac{r^{n+1}}{(r^2+1)^{n+2}}dr-2\int_{0}^\infty\frac{r^{n+1}}{(r^2+1)^{n+3}}dr$$

Now $$\int\frac{r^{n+1}}{(r^2+1)^{n+2}}dr=\frac1{(r^2+1)^{n+2}}\int r^{n+1} dr-\int\left(\frac{d\frac1{(r^2+1)^{n+2}}}{dr}\int r^{n+1} dr\right)dr$$

$$=\frac{r^{n+2}}{(n+2)(r^2+1)^{n+2}}-\int\left( \frac{-(n+2)2r}{(r^2+1)^{n+3}}\cdot\frac{r^{n+2}}{n+2} \right)dr$$ $$=\frac{r^{n+2}}{(n+2)(r^2+1)^{n+2}}+2\int\frac {r^{n+3}}{(r^2+1)^{n+3}}dr$$ (assuming $n+2\ne 0$)

So, $$I=\int\frac{r^{n+1}}{(r^2+1)^{n+2}}dr$$ $$=\frac{r^{n+2}}{(n+2)(r^2+1)^{n+2}}+2\int\frac {r^{n+3}}{(r^2+1)^{n+3}}dr-2\int\frac{r^{n+1}}{(r^2+1)^{n+3}}dr$$ $$=\frac{r^{n+2}}{(n+2)(r^2+1)^{n+2}}+2I$$

So, $$I=-\frac{r^{n+2}}{(n+2)(r^2+1)^{n+2}}$$

Now apply the limit.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.